KNOWLEDGE MONITORING AS A TOOL FOR PROVIDING QUALITY MATHEMATICAL TRAINING OF STUDENTS - Rozumenko , Anzhela; Rozumenko, Anatolii (Physical and Mathematical Education, 2021)
Problem formulation. The article describes the problem of reducing the quality of mathematical training of students of different specialties. Materials and methods. During the preparation of the article the following research methods were used: comparative analysis of the theoretical provisions described in the scientific and educational literature; observation of mathematical training of future specialists in various fields; conversations with students; generalization of pedagogical experience in teaching mathematical disciplines, questionnaires (239 respondents) and statistical methods of experimental data processing (method of statistical hypotheses). Results. Based on the analysis of monitoring research at different levels, it is concluded that the quality of mathematical training of future professionals has a tendency to decrease not depending on the training direction. The results of the experimental regional study, which confirm this conclusion, are presented. The necessity of mathematical knowledge monitoring, as one of the tools to ensure higher level of mathematical training of students, is justified. Methodical recommendations on improving the quality of mathematical preparation for the first-year students of different directions are offered. Conclusions. It was confirmed that the monitoring system should be comprehensive and conducted at all levels of educational management as a guarantee of validity, reliability, economy, integration and practicality. Monitoring of students’ academical achievements is a tool that allows to provide high quality mathematical training for future professionals. The implementation of the experimental study made possible to identify the lack of consistency between the results of the external evaluation, school average score in mathematics and results of the mathematics exam of first-year students of different universities. To avoid gaps and correct the knowledge of freshmen, it is advised to organize during the first semester a repetitive course of school mathematics, which task is to generalize and systematize the basic facts of arithmetic, geometry, algebra and the beginnings of analysis. This will improve the quality of mathematical training of students of higher education institutions.